2018
DOI: 10.1590/1806-9061-2018-0756
|View full text |Cite
|
Sign up to set email alerts
|

Organic Egg Production, Egg Quality, Calcium Utilization, and Digestibility in Laying Hens Fed with Mushroom (Flammulina velutipes) Stem Waste

Abstract: The possibility of using mushroom (Flammulina velutipes) stem waste (FVW) in layer diets was explored in this study. A total of 180, 40-weekold ISA Brown laying hens were randomly assigned to 5 groups, with 6 replications of 6 birds for each group. Layers were fed a standard basal diet as control; antibiotic (0.05% flavomycin); 2% FVW; 4%FVW; and 6% FVW. No significant differences (p>0.05) were observed on hen daily egg production, egg weight, egg mass, unmarketable eggs, feed intake, feed conversion ratio, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Dietary inclusion of herbs and their extracts has growth-promoting roles in poultry [3]. Furthermore, different natural medicinal plants and their extracts as feed supplements have been used as a substitute for antibiotics in poultry production [4,5]. In addition, Mahfuz et al [6] reported that poultry scientists are now dedicated to applying unconventional natural feed supplement, which may play a role in possible therapies to improve the health as well as production performance of chickens.Thus, poultry researchers are searching for potential natural feed resources that will be both environmentally friendly and safe for human society [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary inclusion of herbs and their extracts has growth-promoting roles in poultry [3]. Furthermore, different natural medicinal plants and their extracts as feed supplements have been used as a substitute for antibiotics in poultry production [4,5]. In addition, Mahfuz et al [6] reported that poultry scientists are now dedicated to applying unconventional natural feed supplement, which may play a role in possible therapies to improve the health as well as production performance of chickens.Thus, poultry researchers are searching for potential natural feed resources that will be both environmentally friendly and safe for human society [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the overuse of antibiotics may lead to antibiotic-resistant genes which spread extensively by promoting the selection of antibiotic-resistant bacteria in host animals (Zhou et al, 2016). In addition, the constant application of antibiotics in poultry feed with the purpose to improve production performance has led to human health hazards (Mahfuz et al, 2018). Therefore, it was urgent to find antibiotic substitutes, optimize the composition of intestinal flora, and promote the health of the birds.…”
Section: Effects Of Flammulinavelutipes Stem Base On Microflora and Vmentioning
confidence: 99%
“…Eggs continue to be a well-liked food in every nation, and the egg industry is a significant component of the global food economy. Egg-based products are equally important because they provide additional nutrients and tastes ( Mahfuz et al, 2018 ; Maslova et al, 2020 ; Swanson et al, 2011 ). Several preservation methods extend the shelf life during egg product processing.…”
Section: Introductionmentioning
confidence: 99%